1996
DOI: 10.1097/00005537-199604000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Supracricoid Partial Laryngectomy After Failed Laryngeal Radiation Therapy

Abstract: Twelve patients managed with supracricoid partial laryngectomies (SCPLs) after failed laryngeal radiation therapy (RT) were evaluated. None of the recurrent tumors were amenable to vertical or horizontal partial laryngectomy. Results were analyzed for tracheostomy decannulation, oral alimentation, morbidity, local control, and survival. Major complications included perichondritis (2 patients), laryngeal stenosis (2 patients), and pneumonia from aspiration (1 patient). Mucocutaneous fistula and cricoarytenoid j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
136
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 34 publications
10
136
1
2
Order By: Relevance
“…[20][21][22] Laccourreye et al 20 reported an excellent local control rate (98.2% at 5 years) in cases of T1 to T2 glottic carcinoma with extension to the anterior commissure treated with SCPL. Chevalier and Piquet, 21 in a review of 61 patients with supraglottic squamous cell carcinoma classified as T1 to T4, reported a 97% local control rate after CHP.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Laccourreye et al 20 reported an excellent local control rate (98.2% at 5 years) in cases of T1 to T2 glottic carcinoma with extension to the anterior commissure treated with SCPL. Chevalier and Piquet, 21 in a review of 61 patients with supraglottic squamous cell carcinoma classified as T1 to T4, reported a 97% local control rate after CHP.…”
Section: Commentmentioning
confidence: 99%
“…Recently, SCPL was also reported to be a possible modality of laryngeal preservation treatment in selected patients with local failure after laryngeal radiation therapy. 22 Such data led Bridger 23 to assert that "in the near future any patient being evaluated for total laryngectomy should be considered for the less radical supracricoid partial laryngectomies. "…”
Section: Commentmentioning
confidence: 99%
“…Since second mid-nineties, several authors [5,10,11] have proposed in selected cases salvage partial laryngectomies (SPLs), that include supracricoid partial laryngectomy (SCPL, such as cricohyoidopexy, cricohyoidoepiglottopexy, tracheohyoidopexy, tracheohyoidoepiglottopexy) and endoscopic CO2 laser cordectomy, as an alternative to STL in the treatment of laryngeal recurrence after RT, allowing to preserve laryngeal functions [10]. Even if the common indications for salvage laryngeal surgery after radiotherapy treatment are the same of those recommended for primary laryngeal cancer treatment, the correct staging of the recurrent tumour is the real challenge to select the most suitable surgical indication.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] SCPLs (including both SCPL with cricohyoidoepiglottopexy, or CHEP, and SCPL with cricohyoidopexy, or CHP) can be adopted in many mid-sized laryngeal cancers, strictly respecting tumor-and patient-related indications. 24 The aim of this study was to retrospectively evaluate the oncologic and functional outcomes as well as the complication rate in a multi-institutional Italian cohort of 78 consecutive patients who underwent SCPLs with CHP or CHEP as salvage treatment after RT failure.…”
mentioning
confidence: 99%